Drivers of global Scolytinae invasion patterns - Lantschner, Maria Victoria (2020)
Biological invasions are affected by characteristics of invading species, strength of pathway connectivity among world regions and habitat characteristics of invaded regions. These factors may interact in complex ways to drive geographical variation in numbers of invasions among world regions. Understanding the role of these drivers provides information that is crucial to the development of effective biosecurity policies. Here we assemble for the first time a global database of historical invasions of Scolytinae species and explore factors explaining geographical variation in numbers of species invading different regions. This insect group includes several pest species with massive economic and ecological impacts and these beetles are known to be accidentally moved with wood packaging in global trade. Candidate explanatory characteristics included in this analysis are cumulative trade among world regions, size of source species pools, forest area, and climatic similarity of the invaded region with source regions. Species capable of sib-mating comprised the highest proportion on nonnative Scolytines, and these species colonized a higher number of regions than outbreeders. The size of source species pools offered little power in explaining variation in numbers of invasions among world regions nor did climate or forest area. In contrast, cumulative trade had a strong and consistent positive relationship with numbers of Scolytinae species moving from one region to another, and this effect was highest for bark beetles, followed by ambrosia beetles, and was low for seed and twig feeders. We conclude that global variation in Scolytine invasions is primarily driven by variation in trade levels among world regions. Results stress the importance of global trade as the primary driver of historical Scolytinae invasions and we anticipate other hitchhiking species would exhibit similar patterns. One implication of these results is that invasions between certain world regions may be historically low because of past low levels of trade but future economic shifts could result in large numbers of new invasions as a result of increased trade among previously isolated portions of the world. With changing global flow of goods among world regions, it is crucial that biosecurity efforts keep pace to minimize future invasions and their impacts.